(untitled) (Práxis Educativa, 2025)
The aim of this article was to analyze self-assessment as a formative and critical process in stricto sensu graduate programs organized in cooperation networks among institutions. Using a qualitative approach, the study was based on the analysis of the following documents: National Graduate Plan (2024–2028), Self-Assessment System, and Self-Assessment Technical Report of the Professional and Technological Education Graduate Program (ProfEPT, acronym in Portuguese), for the period 2017 to 2020. Theoretical contributions from Saul (2001, 2003, 2007), Leite (2005, 2008, 2010), Leite et al. (2023), Verhine (2010, 2012), and Rowe and Frewer (2005) supported the analysis of the epistemological, ontological, and axiological assumptions of graduate self-assessment, as well as the conceptions of democratic management, participation, and emancipation. The research findings highlight the contradictions of an evaluation culture based on indicators and productivity metrics. This perspective, grounded in competitive and reductionist rationality, shows limited dialogue with the critical and emancipatory production of scientific knowledge. Keywords: Self-assessment. Graduate programs in networks. Democratic management. Emancipation.